Studies in cardiomyopathy: looking beyond the familiar - Ntusi, Ntobeko A B (Division of Cardiology, 2017)
Background: Little is known about the mechanisms, clinical characteristics, natural history and outcomes of cardiomyopathy amongst Africans. Familial aggregation of cardiomyopathy has not been studied systematically in an African setting. Further, it is not clear whether the various phenotypic expressions of cardiomyopathy represent disparate clinical entities, or whether they are merely different forms of the same disease manifested differently in different circumstances. Methods: Two cohorts of patients with cardiomyopathy were utilised for this study: (1) patients with cardiomyopathy seen at the specialist cardiomyopathy clinic at Groote Schuur Hospital, Cape Town between February 1, 1996 and December 31, 2009; and (2) a group of hypertrophic cardiomyopathy (HCM) patients and first degree relatives seen in a specialist cardiogenetic clinic at Tygerberg Hospital, who underwent cardiovascular magnetic resonance (CMR) imaging at Groote Schuur Hospital.